2005
DOI: 10.1039/b506265a
|View full text |Cite
|
Sign up to set email alerts
|

A simple synthesis of mesoporous carbons with tunable mesopores using a colloidal template-mediated vapor deposition polymerization

Abstract: Mesoporous carbons with highly uniform and tunable mesopores were fabricated by one-step vapor deposition polymerization (VDP) using colloidal silica particles as templates and polyacrylonitrile (PAN) as a carbon precursor.Mesoporous carbons are used as catalysts, adsorbents and various supports. In particular, mesoporous carbons with narrow pore size distributions and tunable pore sizes are important in the field of size-selective separation, and can be applied as packing materials in chromatography or size-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…Furthermore, a porous structure with interconnected pore was retained after the introduction of the PPy layer. This retained pore system is considered to be favorable for mass diffusion of guest molecules [13].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, a porous structure with interconnected pore was retained after the introduction of the PPy layer. This retained pore system is considered to be favorable for mass diffusion of guest molecules [13].…”
Section: Resultsmentioning
confidence: 99%
“…The detailed method and procedure for the preparation of porous carbon and its modification were reported by our previous publications [13,22]. In the functionalization of porous carbon, pyrrole monomers were introduced into a reactor containing a variable amount of porous carbon at room temperature under reduced pressure, and then vaporized by heating at 90 • C [23].…”
Section: Preparation Of Polypyrrole-impregnated Porous Carbonmentioning
confidence: 99%
See 1 more Smart Citation
“…Jang and his co-workers also reported the synthesis of mesoporous carbons via vapor deposition polymerization of polyacrylonitrile on the surface of silica particles. [39] Lu et al reported an aerogel-based approach to synthesize spherical mesoporous carbon particles. [40] In the synthesis, an aqueous solution containing sucrose and various silica templates was passed through an atomizer and dispersed into aerogel droplets.…”
Section: Mesoporous Carbons With Disordered Pore Structuresmentioning
confidence: 99%
“…Previously, it has been demonstrated that the size of these windows could be facilely adjusted by varying the degree of contact among silica spheres through careful control of the sintering temperature [38]. Since the capillary evaporation in the desorption branch of the N 2 isotherm is associated with the structural 'win- dows' among the primary mesopores [37,39], one should be able to evaluate the size of the 'windows' by the PSD derived from the desorption branch, as shown in Fig. 4b.…”
Section: Resultsmentioning
confidence: 99%